Forma da paisagem como critério para otimização amostral de latossolos sob cultivo de cana-de-açúcar - Montanari, Rafael [UNESP]; Marques Jr., José [UNESP]; Pereira, Gener Tadeu [UNESP]; Menezes De Souza, Zigomar [UNESP] (My University, 2005)
The number of sampling points is essential to establish an evaluation program of the spatial variability of soil atribute. The objective of this work was to use the form of landscape as auxiliary criterion in the optimization of the outline sample for the estimate of chemical attributes of oxisol, in a area under sugarcane cultivation. It was possible to choose a continuous area with two landforms: concave, that occur in higher positions of the area, and linear, comprising steep, stocking leans and inferior leans. A 50x50 m spacing in a mesh of 300x3.000 m (total area 94 ha), with 421 sampling points were used. Soil sample in depths 0.0-0.2 m and 0.6-0.8 m were collected, in each point of the grid, in order to evaluate the soil chemical attributes. In the concave landform, larger space variability was observed for the chemical attributes of the soil. The application of the program Sanos 0.1 in the sampling grid (concave landform and linear landform) allowed to observe that the landform concave in both depths presents larger space variability of the chemical attributes than the linear landform.
Landscape form as a criterion for sampling optimization of an oxisol under cultivation of sugar cane
Keywords: Geostatistics; Relationship soil-relief; Soil sampling; Spatial variability